A LEGALITY OF AGENT/DISTRIBUTOR ACTIVITIES IN THE PERSPECTIVE OF CIVIL LAW - Nainggolan, Bernard (Advances in Social Sciences Research Journal, 2020)
Agency/distributorship is a marketing tool in an economic system that is felt to be effective and efficient in relation to marketing networks. Normally, the regulation of agent and distributor activities has not been regulated in a specific formal law but is spread in various laws and regulations at the level of Regulations or Ministerial Decrees which do not specifically regulate agency or distributor activities. From the perspective of civil law, the validity of agency and distributor activities is based on Article 1338 of the Commercial Law Book. as the principle of freedom of contract which regulates the rights and obligations of parties in an agency/distributor agreement, namely between a business actor or principal and an agent or distributor.